MODELLING ETHANOL-WATER PRESSURE SWING DISTILLATION IN AN STRUCTURED PACKED BED COLUMN - Palomino l., Alfredo (2013)
Applying the method of pressure swing distillation (PSD) we obtained (97 % v/v) ethanol starting from 95 % v/v ethanol, which shows that the ethanol-water azeotrope has been broken in this study. Experimental work to achieve the final product was carried out operating !he column in two stages or modes, these being: (1) Low pressure distillation (LPD), and (2) High pressure distillation (HPO). In the first operating mode, a low degree industrial alcohol (80 % v/v ethanol) is fed to a bench scale distillation column packed with Mellapack structure, where (95 % v/v) ethanol is obtained, working at atmospheric pressure. Then product collected in !he first stage is fed to the reboiler, and !he HPD process takes place to get 97 % (v/v) ethanol. Here we have shown that it is possible to perform the pressure swing using an auxiliary engineered device, instead of using a second distillation column, in contras! to the opinion of Doherty and coworkers (2001). As part of this work we also have shown how to exploit the pressure sensitive property of an azeotropic mixture, as it is the case of !he ethanol-water mixture. The ratio of the volume of product obtained to !he energy consumption is 0.7 L. et-OH (97 %)/kWh.